The Pattern of Repetition in Teaching According to Deuteronomy 6:7-9 - Simanjuntak, Harlinton (Sekolah Tinggi Teologi Trinity Parapat, 2024)
One of the problems in Christian families occurs when parents shift the responsibility of educating their children to educational institutions. Even if they finally realise the biblical guidance that parents are responsible for educating their children, they do not understand the method of teaching in the home. The biblical text, Deuteronomy 6:7-9, primarily addresses this issue. The purpose of this study is to show the pattern of repetition as a method of teaching in the household of God's people. The research was conducted by applying exegetical procedures to the target passage, aided by a literature review. Biblical commentaries and biblical journal articles were used to interpret the meaning of the passage. An exploration of the target passage shows that the household teaching method mandated in Deuteronomy 6:7-9 is based on love for God and has three important components: the discipline of repetition, fellowship with God, and social norms in the community. Ultimately, the simple repetition method is effective in cultivating children's spirituality.